2015
DOI: 10.14746/ssllt.2015.5.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Parental visions of their children’s future as a motivator for an early start in a foreign language

Abstract: This paper reports on the qualitative part of a project investigating parental educational aspirations as manifested by enrolling their children (aged 3-6) into very early L2 instruction. The concept of educational aspirations is widely studied in educational psychology as well as in sociology and pedagogy. In SLA, these aspirations can fit in the new framework of imagery and creating visions as they are a part of an ideal L2 self. Data analysis concludes that parental visions towards their children’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The children tended to be more anxious than their peers in programs with less exposure to and insistence on “English only”. In Poland, Rokita-Jaśkow (2013, 2015) also revealed a complex picture resulting from interactions across parents’ aspirations, their choice of public or private preschools, English teachers’ beliefs and competences, and differences in children's learning opportunities. Parents’ previous language learning experiences impacted their decisions as to how early they wanted their offspring to start English and in what program: the less successful as L2 learners the parents themselves were, the more they believed in earlier and more intensive programs (Rokita-Jaśkow, 2015).…”
Section: Language Policy Documents On Preschool Fl Teaching and Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…The children tended to be more anxious than their peers in programs with less exposure to and insistence on “English only”. In Poland, Rokita-Jaśkow (2013, 2015) also revealed a complex picture resulting from interactions across parents’ aspirations, their choice of public or private preschools, English teachers’ beliefs and competences, and differences in children's learning opportunities. Parents’ previous language learning experiences impacted their decisions as to how early they wanted their offspring to start English and in what program: the less successful as L2 learners the parents themselves were, the more they believed in earlier and more intensive programs (Rokita-Jaśkow, 2015).…”
Section: Language Policy Documents On Preschool Fl Teaching and Learningmentioning
confidence: 99%
“…The impact of very YLs’ parents on preschool FL learning is an emerging research topic contributing to deeper understanding of complexities of learning an additional language at preschool age. Comprehensive research on Polish EFL preschoolers (Rokita, 2007; Rokita-Jaśkow, 2013, 2015) showed that most parents were aware of the value of education, thought FL learning was easy for young children and believed that starting early would secure success in their children's FL learning. They attached an instrumental value to knowledge of English, while knowledge of a second FL (mostly French in the Polish context) was associated with cultural value.…”
Section: Empirical Studies On Preschool Fl Programsmentioning
confidence: 99%
“…The climate of interculturalism coupled with introducing English as the most widely taught foreign language in public education turned attention to the importance of plurilingual competence and generated the need for teaching English to children at an early age even in Hungary where monolingualism used to be the norm. Parents more than ever tended to feel responsible for providing their children English language learning opportunities, seeing these as an important investment for their children's future by giving them an intellectual asset for achieving educational success and better life prospects (Rokita-Jaśkov, 2015).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…On the microscale these are the young child's parents that play the most important role in early foreign language education. First of all, it is them who decide to enroll their children to such instruction, which often reflects their aspirations and visions of their children's future (Rokita-Jaśkow, 2015. Class differences, partly marked by parents' own knowledge of foreign languages and their socioeconomic (henceforth SES) status, proved to be a discriminating factor in shaping parental visions of their children's future.…”
Section: The Ecological Approachmentioning
confidence: 99%